2017
DOI: 10.18805/ijar.b-3363
|View full text |Cite
|
Sign up to set email alerts
|

Association of milk quality parameters with teat and udder traits in Tharparkar cows

Abstract: The present experiment was carried out to study the association of milk quality traits (fat, protein, lactose, solid not fat (SNF), total solids (TS) and somatic cell count (SCC)) with teat traits ((teat length (TL), teat diameter (TD), distance between teats (DbT) and teat tip height from ground (THFG)) and udder traits ((udder circumference= UC, udder depth (UD), udder width (UW) and udder height from ground (UHFG)), in Tharparkar cows. The experiment was carried out on 32 tharparkar cows of different pariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Despite nipple attributes being directly related to milk quality in goats, as previously suggested, studies have focused rather on the relationship between the technological features of the udder in terms of its adaptability to milking machines, and the relationship of nipple position with dairy production-related traits is infrequent. In this context, the relationship between udder conformation traits and milk composition-and as a consequence, its effects on milk quality-was supported by the findings of the study by Wagay, et al [37]. These authors suggested that animals presenting thinner teats and less fore-udder depth will produce milk with higher fat and solids-not-fat (SNF) percentages, while animals with teats held high from the ground and deeper and wider udders will produce healthy milk with a lower somatic cell count, which may imply a potential relationship between nipple attributes-especially, nipple diameter and milk quality-in cattle.…”
Section: Discussionsupporting
confidence: 58%
“…Despite nipple attributes being directly related to milk quality in goats, as previously suggested, studies have focused rather on the relationship between the technological features of the udder in terms of its adaptability to milking machines, and the relationship of nipple position with dairy production-related traits is infrequent. In this context, the relationship between udder conformation traits and milk composition-and as a consequence, its effects on milk quality-was supported by the findings of the study by Wagay, et al [37]. These authors suggested that animals presenting thinner teats and less fore-udder depth will produce milk with higher fat and solids-not-fat (SNF) percentages, while animals with teats held high from the ground and deeper and wider udders will produce healthy milk with a lower somatic cell count, which may imply a potential relationship between nipple attributes-especially, nipple diameter and milk quality-in cattle.…”
Section: Discussionsupporting
confidence: 58%